Pragmatic issues and prescribing patterns in bipolar disorder: A mental health professional's survey - Shobit Garg; Nishant Goyal; Sai Krishna Tikka; Preeti Mishra (Industrial Psychiatry Journal, 2022)
Background: There is substantial treatment gap between the suggested guidelines and pragmatic clinical practice for psychotropic usage in bipolar disorder (BD) due to the lack of naturalistic studies and not taking into account the transcultural differences and diverse background. We intend to study this treatment gap and elucidate the preference of psychotropics and prescription patterns, critical clinical issues faced and related pragmatics in BD by conducting the mental health professionals survey. Methodology: After focused discussions, Canadian Network for Mood and Anxiety Treatments guidelines being the primary anchor, a 46-item online survey questionnaire was prepared. With 25.4% response rate, 127 psychiatrists were evaluated using Survey Monkey® electronic platform on the demographics, predominant polarity; usage of antipsychotics, antidepressants, and electroconvulsive therapy, psychotropic's preference (monotherapy vs. polytherapy) in the acute and maintenance phase of BD. Results: Majority of the participants were males (70.9%) and placed in government institute or medical colleges. Majority agreed that child and adolescent and old age bipolar probands are not routinely seen but subthreshold BD cases are frequent; did not prefer mood stabilizer in pregnancy (61.4%) and antidepressants, preferred polytherapy in acute but monotherapy in maintenance phase (after 3rd episode), seldom preferred ECT as an option (more in suicidality), agreed to a subset of BD being refractory and neuroprogressive. Conclusion: This study elucidates the importance of treatment preferences, prescribing patterns and pragmatic issues faced by the clinicians. These patterns if studied longitudinally in a systematic manner would help in modifying the potential treatment strategies and reduce treatment gap.